2013
DOI: 10.3168/jds.2012-5943
|View full text |Cite
|
Sign up to set email alerts
|

Association between dry period length and lactation performance, lactation curve, calf birth weight, and dystocia in Holstein dairy cows in Iran

Abstract: In this study, 65,971 lactations on 41,842 cows in 64 herds were used to determine the association between dry period length (DPL) and lactation performance, lactation curve, calf birth weight, and the incidence of calving difficulty during the subsequent parity in Holstein dairy cows in Iran. The length of the dry period was classified into 7 categories: 0 to 35d, 36 to 50d, 51 to 60d, 61 to 70d, 71 to 85d, 86 to 110d, and 111 to 160d. Cows with the standard DPL (51 to 60d) produced more 305-d milk, fat, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
37
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 28 publications
6
37
0
3
Order By: Relevance
“…Collier et al (2012) reported that the required length of dry period for the first parity cows is 60 d, while for the second parity and older cows it can be reduced to 30 d with no negative effect on production and health. On the other hand, Atashi et al (2013) showed that third parity and older cows need longer dry periods compared with younger animals. Khazanehei et al (2015) suggested that this difference between parity groups might be due to differences in growth and fat deposition between the first and second parity cows compared with the older cows.…”
mentioning
confidence: 99%
“…Collier et al (2012) reported that the required length of dry period for the first parity cows is 60 d, while for the second parity and older cows it can be reduced to 30 d with no negative effect on production and health. On the other hand, Atashi et al (2013) showed that third parity and older cows need longer dry periods compared with younger animals. Khazanehei et al (2015) suggested that this difference between parity groups might be due to differences in growth and fat deposition between the first and second parity cows compared with the older cows.…”
mentioning
confidence: 99%
“…Ten eerste, zijn effecten van droogstandslengte op persistentie van de melkproductie in de volgende lactatie tot nu toe onduidelijk (Mantovani et al, 2010;Atashi et al, 2013;Chen et al, 2016a). Bovendien kan verondersteld worden dat aanpassingen in het rantsoen de persistentie van koeien met een verkorte of geen droogstand kunnen verbeteren.…”
Section: Droogstand Op Maat -Algemene Inleiding Achtergrondunclassified
“…reported that omitting the DP resulted in an earlier time of peak yield (PT), lower PY, and lower LP in a small study (n = 17). On the contrary, Atashi et al (2013) found that a shortened DP (0 to 35 d) was associated with later PT, lower PY, and higher LP in a field study, compared with a conventional DP (50 to 60 d). In addition, both studies did not investigate effects of DP length on lactation curve characteristics in multiple lactations.…”
Section: Introductionmentioning
confidence: 72%
“…reported that omitting the DP resulted in an earlier PT, lower PY, and lower LP in a small study (n = 17) compared with a conventional DP. Atashi et al (2013) found that a shortened DP (0 to 35 d) was associated with later PT, lower PY, and higher LP in a field study compared with a conventional DP (50 to 60 d). The number of animals used in the study of was relatively low (n = 17) and the filed study of Atashi et al (2013) was not a preplanned experiment, which might bias the results.…”
mentioning
confidence: 80%
See 1 more Smart Citation